Strengthening the Professional Ethics of University Teachers for Quality Assurance in Nigerian Education - Emenalo, F.C. (International Journal of Educational Management, 2022)
This paper focuses on the strengthening of the professional ethics of university teachers to ensure quality assurance in Nigerian education. The importance and indispensability of quality education preceded by quality assurance in Nigeria universities are stressed. The responsibilities and roles of the universities and the teachers in the overall sustainable development of the students and nation as well as the inculcation of the right type of values to the students for proper social formation, for peaceful co-existence and democratic living were discussed. The prevailing unprofessional conducts of most university teachers were decried and what constitutes unprofessional ethics and ways of strengthening the professional ethics were x-rayed.